Posted by **Margie** on Friday, June 29, 2007 at 5:49pm.

Solve the following quadratic by either factoring or using the quadratic formula:

6x2 - 5x = 6

6x^2 -5x -6 = 0

(3x+2)*(2x-3) = 0

Take it from there

## Answer this Question

## Related Questions

- Algebra - Solve the equation. Use factoring or the quadratic formula, whichever ...
- Math - A: Solve the following equation: k2 + 4k = 0 A: By factoring B: By using ...
- algebra - 0. Tell your classmates about your pet to set up the scenario for ...
- math - A: Solve the following equation: k2 + 4k = 0 A: By factoring B: By using ...
- Math - Use the quadratic formula to solve each of the following quadratic ...
- Math - Solve for the zeros of the function using the quadratic formula. 3x^2=-4x...
- College Math II - Solve by using the quadratic formula. x^2 + 6x + 6 = 0 I am ...
- algebra - Solve the following equation: k2 + 4k = 0 By factoring and By using ...
- algebra - Quadratic equations can be solved by graphing,using the quadratic ...
- math algebra - Part 1: Which part of the quadratic formula tells you whether the...